Mechanical, Thermal, and Optical Properties of MoTe2 and MoSe2 Monolayer TMDCs Materials: First-Principles Study - Neupane, Tejendra; Pokharel, Arpan; Khanal, Kamal; Yadav, Sukrit Kumar; Paudel, Ganesh; Rijal, Om Shree; Neupane, Hari Krishna (Journal of Institute of Science and Technology, 2025)
Materials can be used in the fields of electronic, optoelectronics, and thermoelectric devices based on their electronic, optical, mechanical and thermal properties. In this study, we explored the mechanical, thermal, and optical properties of MoSe2 and MoTe2 materials computationally, using density functional theory (DFT) method through quantum ESPRESSO computational software package. For the investigation of materials mechanical properties, their elastic constants and modulus of rigidities are analyzed. It is found that MoSe2 and MoTe2 have brittle, soft, and compressible properties. Both have anisotropic tendencies as suggested by Chung-Buessem anisotropic ratio. Phonon velocities, and Debye temperature of MoSe2 and MoTe2 are examined for the prediction of their thermal properties. Both materials have good thermal properties. Complex dielectric function has been deployed for the analysis of materials optical properties. The nature of different optical curves such as optical conductivity, absorption coefficient, transmission coefficient, and reflection coefficient (reflectivity) is studied from complex dielectric functions and found that both materials have optical anisotropy nature with greater degree of polarization in xx- & yy- plane than in zz-plane. Moreover, materials have semiconducting properties based on their absorption coefficient plots. They also have higher transmission occurred at low energy region (up to 1.2 eV), and higher absorption values at energy range (1.10 - 3.5) eV.  The results suggest that MoSe2 and MoTe2 materials can be used as effective absorbent materials in the infrared and visible light regions. Hence, these materials can be used to create more efficient photoelectronic as well as optoelectronic devices.